Analisis Strukturalisme terhadap Makna Kesunyian dalam Puisi Hujan di Bulan Juni Karya Sapardi Djoko Damono - Anggini, Putri; Ripai, Muhammad; Rambe, Nailah Faizah S; Nasution, Azwa Khalisa; Husna, Husna; Amalia, Dhea; Wasilah, Atika (eScience Humanity Journal, 2025)
This study analyzes the representation of solitude in Sapardi Djoko Damono's poem "Hujan di Bulan Juni" (Rain in June) through a structuralist approach.  Its theoretical contribution lies in the systematic application of structural analysis to modern Indonesian lyrical poetry, revealing how intrinsic elements—diction, imagery, figures of speech, rhyme, and typography—interact to form a complex meaning of solitude. This analysis demonstrates how Sapardi's simplicity of language yields profound symbolic meaning, offering an objective interpretive framework free from purely subjective interpretations.  Practically, this research contributes to a deeper understanding of Sapardi's work, particularly "Hujan di Bulan Juni," often considered a representation of solitude and sincerity. The relevance of the theme of solitude is examined within the Indonesian cultural context, specifically the values of inner resilience and humility that resonate strongly with the poem. This study fills a gap in structuralist studies of Sapardi's poetry and enriches the methodology of modern Indonesian literary analysis.